PENGARUH PROBLEM BASED LEARNING TERHADAP KEMAMPUAN BERPIKIR KRITIS MATEMATIS SISWA KELAS III SEKOLAH DASAR - Isti Zulfa Nida; Sukamto; Veryliana Purnamasari (STKIP Subang, 2023)
Critical thinking skills are one of the competencies that need to be developed in today's digital era. In the 21st century, students are required to be able to develop life skills and soft skills including critical thinking skills. Problem Based Learning is a learning model that encourages students to learn and work in groups to solve problems, think critically and analytically. The purpose of this study was to analyze the effect of the Problem Based Learning learning model on mathematical critical thinking skills. The research method used in this research is quantitative. This type of research is an experiment with a Pre-experimental design type of Pretest-Postest One-Group Design. The data collection technique in this study is in the form of a description test which refers to indicators of critical thinking skills. Data analysis was carried out using the normality test to obtain a Sig value of 0.143 which indicates that the data is normally distributed. While testing the hypothesis using the paired sample t-test formula obtained a value of Sig. (2-tailed) of 0.002 is less than the value of 0.050 so that it can be concluded that there is an influence of the Problem Based Learning learning model on the mathematical critical thinking skills of third grade elementary school students.